2016
DOI: 10.1155/2016/5293034
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Test for Simultaneous Bacterial Identification and Antibiotic Susceptibility

Abstract: Background. Elucidation of a pathogen's antimicrobial susceptibility requires subculture after the organism is first isolated. This takes several days, requiring patients to be treated with broad-spectrum antibiotics. This approach contributes to the development of bacterial resistance. Methods. Microtiter wells were coated with a polyclonal antibody targeting the pathogen of interest. Bacterial suspensions were added in the presence/absence of selected antibiotics. After washing, captured bacteria were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In the case of routine methods for AST, it usually takes at least 24 h to obtain growth of bacterial colonies and an additional 24 h to obtain isolate characterization, namely biochemical identification and phenotypic AST (Altaie and Dryja 1994;Faro et al 2016). The methods generally used afford qualitative results, using the susceptible, intermediate or resistant categories, but some of them provide quantitative results, expressed as minimum inhibitory concentration (MIC) (Jenkins and Schuetz 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of routine methods for AST, it usually takes at least 24 h to obtain growth of bacterial colonies and an additional 24 h to obtain isolate characterization, namely biochemical identification and phenotypic AST (Altaie and Dryja 1994;Faro et al 2016). The methods generally used afford qualitative results, using the susceptible, intermediate or resistant categories, but some of them provide quantitative results, expressed as minimum inhibitory concentration (MIC) (Jenkins and Schuetz 2012).…”
Section: Introductionmentioning
confidence: 99%
“…26 Culture methods take long periods of time, initial cultures take 24–48 h (during which time broad-spectrum antibiotics are typically initiated), then following identification of the microbe, antimicrobial susceptibility determination requires another 24–48 h. 27 In a 2015 survey of infectious disease practitioners, 31% reported that they believed patients are treated with incorrect antibiotics during the wait for blood culture results. 28 In addition to long-turnaround times, culture-based methods also have the potential to return false-negative results when samples are obtained after antimicrobial therapy has begun.…”
Section: Diagnostic Tests For the Identification Of Bacterial Pathogensmentioning
confidence: 99%